THE URGENCY OF HALAL CERTIFICATION IN ENSURING LEGAL CERTAINTY FOR MUSLIM CONSUMERS - Marliana, Brian Fina; Rokhim, Abdul; Farahwati (Awang Long Law Review, 2025)
Perceptions about halal certification vary widely, many consumers still do not understand the importance of this certification, even though this certification is part of their rights as consumers. Without a strong understanding of the importance of halal certification, Muslim consumers may face the risk of consuming non-halal products that can interfere with their beliefs. The research method used is Normative legal research, research by approaching laws and regulations and legal literature and journals. The results of the study show that halal certification has a crucial role in providing legal certainty for Muslim consumers in Indonesia, the majority of whom are Muslim. Law No. 33 of 2014 concerning Halal Product Assurance makes this certification mandatory, so it is expected to protect consumer rights in accessing products that comply with sharia principles. Legal certainty for Muslim consumers is very important in the context of consumer protection, especially in the digital era and e-commerce. Research shows that adequate regulation and protection can help Muslim consumers obtain products and services that comply with Islamic principles. Optimizing halal certification is one of the key aspects that supports legal certainty for Muslim consumers. Thus, the urgency of halal certification in this context lies not only in legal and social support, but also in collective efforts to educate the public about the importance of halal products, operationalization in business practices, and assurance that the products they consume maintain sharia values. The role of the government in supporting Micro, Small, and Medium Enterprises (MSMEs) and other business actors to access halal certification is very strategic, considering the importance of this certification to increase the competitiveness of MSME products in domestic and international markets.